Ion Sputtering at Grazing Incidence for SIMS-Analysis - Ryssel, Heiner; Ullrich, M.; Burenkov, Alexander (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2005)
The angular distributions of sputtered atoms at large angle oblique and grazing incidence of the primary ion beam in SIMS-analysis have been simulated. They exhibit distinct arc-like areas of an enhanced sputtering yield in the spherical angular distributions, especially at grazing incidence angles of about 80° from the normal. These arc-like maxima are formed by particles knocked-out from the target as a result of single collisions between primary ions and target atoms. A possibility to use sputtered particles taken only from angles around those arc-like maxima in the angular distribution of sputtered particles for SIMS-analysis and the depth-resolution of the SIMS-analysis for different sputtering conditions was investigated by means of Monte-Carlo simulations. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2017-07-10:Pub.2005.tech.IE.LEB.ionspu
Keywords: Angular distribution; Depth-resolution; Ion sputtering; Monte-Carlo; SIMS